2015
DOI: 10.1016/j.forsciint.2015.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic hair care products may increase false positives in hair drug testing

Abstract: The question of why different races appear more susceptible to hair contamination by external drugs remains controversial. This research studied susceptibility of head hair to external cocaine and methamphetamine when hair products have been applied. Three different chemical classes of ethnic hair products were applied to Caucasian, Asian, and African hair. Some products increased the methamphetamine and cocaine concentrations in all hair types. A unique finding of this research is that certain ethnic hair pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Hair may provide a long-term information of drug intake and toxin exposure, extended from months or even years if the scalp hair is long [58]. However, the limits of such methods are still controversial [59,60] and may be affected by hair care practices. Hair can also be used to sensor air pollution, as pollutants can be absorbed by hair fibers.…”
Section: Trace Elementsmentioning
confidence: 99%
“…Hair may provide a long-term information of drug intake and toxin exposure, extended from months or even years if the scalp hair is long [58]. However, the limits of such methods are still controversial [59,60] and may be affected by hair care practices. Hair can also be used to sensor air pollution, as pollutants can be absorbed by hair fibers.…”
Section: Trace Elementsmentioning
confidence: 99%
“…To date, there has been minimal investigation into the removal of contaminant MA from hair. One study investigated the removal of MA·HCl from cosmetically treated hair, which was decontaminated using either three 5second DCM washes or a 1–2minute dilute shampoo wash . MA removal was unsuccessful and concentrations in hair remained above cut‐off levels.…”
Section: Discussionmentioning
confidence: 75%
“…Another consideration is the applicability of the pooled hair samples used in Studies 1 to 3. Some of the properties of the clinical hair samples that may have affected decontamination effectiveness in this investigation include hair length and regularity of hair hygiene, cosmetic treatments, and hair fiber porosity (as discussed above) . The pooled hair samples included trimmings collected during a haircut, while it is recommended by the SoHT to cut hair samples as close to the scalp as possible .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversially, the ethnicity of testees has also been offered as a reason for false positive tests (for example, http://alwaysstayclean.com). Kidwell, Smith, and Shepherd () demonstrated that some ethnic hair care products can significantly exacerbate the absorption of environmental contaminants and earlier studies measured higher levels of drug uptake into darker hair due to the higher presence of melanin (Cone et al, ; Gygi et al, ; Joseph et al, ). However, a comprehensive laboratory analysis failed to find any statistical correlation between ethnicity and incidence of false‐positive drug tests (Kelly, Mieczkowski, Sweeney, & Bourland, ).…”
Section: Other Potential Methods For Evading Drug Hair Testingmentioning
confidence: 99%